Highly sensitive B, N co-doped carbon dots for fluorescent and colorimetric dual-mode detection of mercury ions in wastewater. Issue 6 (December 2021) - Fu, Qing; Long, Caicheng; Huang, Jiaoyan; Liu, Sicong; Qing, Taiping; Zhang, Peng; Feng, Bo
Abstract: Mercury ions (Hg 2+ ) owing to excessive discharge cause serious damage to human health and the water ecosystem via bioaccumulation in food chains. Novel materials employed for the high-performance monitoring of Hg 2+ are urgently required. Herein, using sucrose, boric acid, and melamine as raw materials, a new nanomaterial sensor, namely boron and nitrogen co-doped carbon dots (B, N-CDs), was designed for fluorescent and colorimetric dual-mode detection of Hg 2+ . Because of the occurrence of both dynamic and static quenching, B, N-CDs were utilized to function as fluorescent sensors for detecting Hg 2+ with a limit of detection (LOD) of 5.3 nM. B, N-CDs performed an action for catalytic oxidation of 3, 3′, 5, 5′-Tetramethylbenzidine (TMB) to a blue cationic radical via peroxidase mimetic activity. By sequentially adding cysteine and Hg 2+ to control the emergence of the TMB cation radical, a sensor for the Hg 2+ assay was established through the colorimetric "on-off-on" signal and the LOD was as low as 7.8 nM. Moreover, the application potential of B, N-CDs for complex water environments was demonstrated to be excellent. In summary, the dual-mode detection method delivers some valid strategies for the detection of mercury in aqueous solutions employing the functional nanomaterials mentioned, and opens new avenues in tackling the problem of heavy metal ion pollution for environmental monitoring and remediation. Graphical abstract: ga1 Highlights: The B, N-CDs exhibited favorable optical properties and catalase activity. Fluorescent and colorimetric dual-mode was applied to detect mercury ions. The method achieved high sensitivity and visible monitoring of Hg 2+ in wastewater.